Analisis Model Bisnis Dengan Pendekatan Business Model Canvas (BMC) dan Penetapan Strategi Pada UMKM di Industri Pariwisata - Evi Sirait; Natalia Kristiani Tandafatu; Fitri Novilia; Donny Juliandri Prihadi; Basnendar Herry Prilosadoso (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to determine and analyze the business model with the Business Model Canvas (BMC) approach and strategy determination in MSMEs in the tourism industry. The type of research used in this study is a descriptive survey. Data collection techniques were carried out using the questionnaire method. Furthermore, the research data was analyzed using three methods consisting of reduction, data presentation and drawing conclusions. The findings in this study are that there are 9 elements owned by the Business Model Canvas (BMC) to help the sustainability of MSMEs in the tourism industry including, Customer Segments, Value Propositions, channels, customer relationships, revenue streams, main activities, main resources, main partnerships and cost structures. In addition, based on the percentage data of respondents' responses about business strategies in MSMEs in the tourism industry is 86%, it means that the response according to respondents is Good. This is expected to be an alternative for business actors in running their business. Determining a good business strategy is important so that a business or business can survive and grow in the midst of tight competition.